Medicinal Potential of Tragia involucrata Linn for Management of Diabetes Mellitus in Kenya, A Review - Onsongo Apiri, Benard; Mae Makonde, Huxley; Piero Ngugi, Mathew; Ogare, James; Mwiti Kibiti, Cromwell (Multidisciplinary Journal of Technical University of Mombasa, 2024)
The increasing prevalence of diabetes mellitus globally, especially in low- and middle-income countries, necessitates the exploration of alternative therapeutic strategies. Tragia involucrata Linn, commonly known as climbing nettle is a plant widely used in traditional medicine, shows significant promise due to its diverse bioactive compounds. This review comprehensively addresses the phytochemical composition, antidiabetic efficacy, antihyperlipidemic properties, and safety profiles of T. involucrata as a potential medicinal plant. This review collaborates the significance of T. involucrata in management of diabetic patients and calls for more clinical research studies to fully harness its benefits and promote the development of plant-based therapies for diabetes in Kenya.